2019
DOI: 10.3758/s13428-019-01230-4
|View full text |Cite
|
Sign up to set email alerts
|

Confounder detection in linear mediation models: Performance of kernel-based tests of independence

Abstract: It is well-known that the identification of direct and indirect effects in mediation analysis requires strong unconfoundedness assumptions. Even when the predictor is under experimental control, unconfoundedness assumptions must be imposed on the mediator-outcome relation in order to guarantee valid indirect-effect identification. Researchers are therefore advised to test for unconfoundedness when estimating mediation effects. Significance tests to evaluate unconfoundedness usually rely on an instrumental vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
(99 reference statements)
2
7
0
Order By: Relevance
“…This procedure was also taken into consideration as different confounders might occur, but it also to previously examine and avoid collinearity across variables. This involved procedures such as evaluating outliers or the independence of linearly uncorrelated residuals as depicted in previous literature (25). The statistical analysis for the mediation model was performed using SPSS 22 (IBM) under the Process macro for SPSS (26) to test the hypothesis that death fear mediates the effect of personality on anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was also taken into consideration as different confounders might occur, but it also to previously examine and avoid collinearity across variables. This involved procedures such as evaluating outliers or the independence of linearly uncorrelated residuals as depicted in previous literature (25). The statistical analysis for the mediation model was performed using SPSS 22 (IBM) under the Process macro for SPSS (26) to test the hypothesis that death fear mediates the effect of personality on anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Next, Direction Dependence Analysis (DDA) was applied to evaluate the most probable causal direction between variables using the SPSS add-ons (publicly available at https://www.ddaproject.com ). The DDA was developed to determine causal relationships 61 63 and has been used effectively in previous studies 64 66 . Specifically, the DDA consists of three components and the target model (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…com). The DDA was developed to determine causal relationships [61][62][63] and has been used effectively in previous studies [64][65][66] . Specifically, the DDA consists of three components and the target model (e.g.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Formal statistical tests for independence that are based on the HSIC (i.e., 𝐻𝐻 0 : 𝐻𝐻𝐻𝐻𝐻𝐻𝐻𝐻 = 0) are also available. In the current study, we apply the asymptotic (gamma-approximated) HSIC test with median heuristic bandwidths (Gretton et al, 2008) as recommended by simulation results from Wiedermann and Li (2019). Selection of causal models I, II and III can be made by conducting HSIC-based independence tests.…”
Section: Independence Properties Of Predictors and Errorsmentioning
confidence: 99%
“…We evaluated four sample sizes in the simulation: 500, 1000, 2000, and 5000. The levels of sample size were selected to reflect a range of small to large samples appropriate for DDA, as previous studies have shown that the HSIC test may require sample sizes in excess of n ≥ 800 to achieve sufficient power (Wiedermann & Li, 2019).…”
Section: Data Generationmentioning
confidence: 99%